Transformation and Historical Trajectory of the Development of Qur’anic Exegesis During Three Islamic Dynasties: Idrīsiyyah, Fāṭimiyyah, and Uthmāniyyah - Mukhlis, Wail; Yardho, Moh.; Salim, Moh. Fuad (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
This article aims to examine the transformation and historical development of Qur'anic exegesis during the reign of three major Islamic dynasties: Idrīsiyyah, Fāṭimiyyah, and Uthmāniyyah. The main research question explores how the patterns, methodologies, and contributions of tafsir evolved within the framework of political authority and socio-historical change. Employing a qualitative method with a historical approach, this study analyzes primary sources from classical tafsir works and secondary references from historical and academic literature. The findings reveal that tafsir underwent significant evolution during each dynastic period. Under the Idrīsiyyah dynasty, exegesis began to be codified with emphasis on Ahl al-Bayt, linguistics, and fiqh. The Fāṭimiyyah era developed theological and esoteric interpretations aligned with Ismaili Shi’ism. Meanwhile, the Uthmāniyyah period marked a diversification of interpretive approaches, including scientific, spiritual, adabī-societal, and legal methodologies, supported by formal institutions. This study concludes that tafsir is a dynamic intellectual product shaped by continuous interaction between the Qur'anic text, its interpreters, and the historical contexts in which they lived.